(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Creativity is the nature that features the distinction between people and different animals of mother earth. It is the force of creative mind that supports the innovative psyche to investigate the skyline and even endeavor to peep past it. Retelling is a particularly innovative action to which one goes over since the prime of his life and keeps on bearing it till, he has the ability to talk, compose or think. In our everyday schedule we run over individuals conveying same episodes with various understandings and point of perspectives over it. In the comparative way, abstract staff has attempted their hands over retelling the notable myths and produce various translations from them. The current exploration work endeavors to investigate the select three works of their separate creators underlining the defilement applied while retelling the notable myths in contemporary settings. This basic examination regards the legendary material as old abstract undertakings and attempts to investigate them searching for the contemporary sensibilities inside them. As far as possible itself to Indian myths and Indian creators. The myths under examination rise out of Mahabharata, the biggest epic which contains different legendary stories identified with one another in without a doubt. Mahabharata is famous in abstract field just as in homegrown area.